1996
DOI: 10.1073/pnas.93.21.11699
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin is required for nursing but is not essential for parturition or reproductive behavior.

Abstract: Oxytocin, a neurohypophyseal hormone, has been traditionally considered essential for mammalian reproduction. In addition to uterine contractions during labor and milk ejection during nursing, oxytocin has been implicated in anterior pituitary function, paracrine effects in the testis and ovary, and the neural control of maternal and sexual behaviors. To determine the essential role(s) of oxytocin in mammalian reproductive function, mice deficient in oxytocin have been generated using embryonic stem cell techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
435
7
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 653 publications
(471 citation statements)
references
References 41 publications
14
435
7
4
Order By: Relevance
“…42 Accordingly, enhanced smooth muscle contractility has been demonstrated after repetitive oxytocin stimulation, presumably mediated by increased sensitivity of OT-R. 43 Still the role of oxytocin in parturition has been questioned as delivery proceeds normally in oxytocin-deficient mice. 44 This finding could be peculiar to mice; however, in our review, five vaginal deliveries were reported suggesting that parturition in humans may be regarded as being independent from circulating oxytocin. Accordingly, it has been postulated that oxytocin from different sources contributes to the various stages of labor, with uterine oxytocin supporting the initiation of parturition and pituitary oxytocin the expulsive phase.…”
Section: Discussionmentioning
confidence: 76%
“…42 Accordingly, enhanced smooth muscle contractility has been demonstrated after repetitive oxytocin stimulation, presumably mediated by increased sensitivity of OT-R. 43 Still the role of oxytocin in parturition has been questioned as delivery proceeds normally in oxytocin-deficient mice. 44 This finding could be peculiar to mice; however, in our review, five vaginal deliveries were reported suggesting that parturition in humans may be regarded as being independent from circulating oxytocin. Accordingly, it has been postulated that oxytocin from different sources contributes to the various stages of labor, with uterine oxytocin supporting the initiation of parturition and pituitary oxytocin the expulsive phase.…”
Section: Discussionmentioning
confidence: 76%
“…One set each was used for V1aR binding, oxytocin receptor (OTR) binding, OT expression, and AVP expression. Sections were processed for receptor autoradiography using I 125 -labeled d(CH 2 ) 5 [Tyr(Me) 2 ,-Tyr-NH 2 9 ]ornithine vasotocin (NEN Life Sciences Products, Boston, MA) for the OTR and (Phenylacetyl 1 ,0-Me-D-Tyr 2 , [ 125 I-Arg 6 ]-) vasopressin (linear), V-1A antagonist (NEN Life Science Products, Boston, MA) for the V1aR as described previously (Nishimori et al, 1996;Young et al, 1997). Slides were exposed to BioMax MR film (Kodak) for 48 h. Results from the V1aR autoradiography were used to confirm genotype.…”
Section: Receptor Autoradiography and In Situ Hybridizationmentioning
confidence: 99%
“…Slides were exposed to BioMax MR film (Kodak) for 48 h. Results from the V1aR autoradiography were used to confirm genotype. Sections were processed for AVP and OT expression using 35 S-labeled antisense oligos as described previously (Nishimori et al, 1996;Young et al, 1996). Slides were exposed to Bio Max MR film (Kodak) for 1-2 h.…”
Section: Receptor Autoradiography and In Situ Hybridizationmentioning
confidence: 99%
“…Although all offspring die shortly after birth because of the dam's inability to provide milk, postpartum injection of OXT into these Oxt-deficient dams restores milk ejection and rescues the offspring (Nishimori et al, 1996). Similarly, Oxtr -/-mice are viable and have no obvious defects in fertility or sexual behavior.…”
Section: Cd38 Knockout Micementioning
confidence: 99%
“…Subcutaneous administration of low doses of OXT also facilitates social recognition (Popik et al, 1992). Two mouse models with either OXT or OXT receptor (OXTR) gene knockouts (Oxt / or Oxtr / , respectively) show signs of profound social amnesia (Nishimori et al, 1996;Ferguson et al, 2000;Takayanagi et al, 2005;Crawley et al, 2007;Macbeth et al, 2010;Sala et al, 2011), which was rescued in the OXT knockout mice by the administration of OXT. These observations suggest that OXT plays an important role in social behavior via the stimulation of the OXTR during brain development and throughout the juvenile and adult life-stages (Ahern and Young, 2009;Carter et al, 2009;Insel, 2010).…”
Section: Introductionmentioning
confidence: 99%